1019 OSA correction with Torus Mandibularis Resection. (12th April 2019) - Pierson, Grant; Nazir, Usman
Abstract: Introduction: Obstructive sleep apnea (OSA) is a rising issue world-wide. Oral anatomical anomalies are being linked to OSA. Obstruction of the oropharyngeal passage by any form: bony growth, increased tissue, over-relaxation, or genetically smaller maxillofacial features increase the risk of OSA. We present a patient that demonstrates resolution of OSA after successful surgical correction and the addition of an oral appliance after failing continuous positive airway pressure (CPAP) therapy. Report of Case: 47-year-old female complained of sleep disturbance for her entire life with snoring, nocturnal arousals and daytime sleepiness. Home sleep apnea testing (HST) demonstrated moderate OSA with apnea-hypopnea index (AHI) 26.5. Patient was unable to tolerate CPAP therapy. Physical exam revealed bony prominences in the floor of the patient's mouth. Patient underwent surgical resection of the torus mandibularis. After oral surgery a repeat HST with an oral appliance was performed showing resolution of patient's OSA with AHI 1.6. Conclusion: Due to the increase in diagnosis of sleep apnea. More patients are unable to tolerate PAP therapy. A complete oral examination is an important aspect in evaluating patients for sleep apnea. Surgical correction of torus mandibularis with the addition of an oral appliance was effective in treating this patient's moderate OSA.